Sistem Informasi Pariwisata Berbasis Web Kelurahan Batuputih Bawah Kota Bitung: Web-Based Tourism Information System for Batuputih Bawah Subdistrict-Bitung City - Pinontoan, Benny; Titaley, Jullia; Weku, Winsy Christo Dailan (Sam Ratulangi University, 2025)
This study aims to develop a web-based tourism information system specifically for Batuputih Bawah subdistric in Bitung City, which is know for its natural attraction. The information system is intended to serve as an accessible and interactive platform for tourists, providing comprehensive information about local tourist destinations, visitor guidelines and conservation initiatives. Data were collected through interviews with local authorities, resident and destination caretaker, along with field observations to obtain detailed information about the tourist spots and supporting facilities. The system was developed using a Research and Develoment (R&D) approach, which included requrement analysis, system design and iterative testing phases to ensure usability and relevance. The result indicate that the web-based tourism information system effectively provides users with an integrated source of destination details, route maps, booking options and guidelines for observing local wildlife, particulary for Yaki conservation. Through this platform, it is expected that Batuputih Bawah can increase tourism interest while promoting environmental sustainability and awareness among visitors. The website not only acts as a promotional tool but also fosters sustainable touris practices by engaging tourists in local conservation effort. ABSTRAK Tujuan pengabdian ini untuk mengembangkan sistem informasi pariwisata berbasis web untukKelurahan Batuputih Bawah Kota Bitung yang dikenal dengan daya tarik wisata alamnya. Sisteminformasi ini diharapkan dapat menjadi platform yang mudah dikasesdan interaktif bagi wisatawan,dengan menyediakan informasi lengkap mengenai destinasi lokal, panduan kunjungan serta inisiatifpelestarian. Data dikumpulkan melalui wawancara dengan pihak berwewenang setempat, warga danpetugas destinasi serta observasi lapangan untuk mendapatkan informasi detail mengenai objek wisatadan fasilitas pendukungnya. Sistem ini dikembangkan menggunakan pendekatan Research andDevelopment (R&D) yang mencakup analisis kebutuhan, perancangan sistem dan pengujian berulanguntuk memasyikan kegunaan dan relevansi. Hasil pelaksanaan pengabdian menunjukan bahwa sisteminformasi ini efektif menyediakan sumber informasi yang terpadu bagi pengguna seperti detail destinasi,peta rute, opsi pemesanan dan panduan untuk pengamatan satwa khususnya untuk pelestarian yaki.Website ini tidak hanya berfungsi sebagai alat promosi, tetapi juga mendorong praktik pariwisataberkelanjutan dengan melibatkan wisatawan dalam upaya konservasi lokal.